(untitled) (Research, Society and Development, 2022)
Introduction: Child sexual violence is highlighted among all violence committed in children, mainly because of its moral content, which involves from the family relationship to the involvement of the health team. Although not the most frequent, child sexual violence has often irreversible consequences that result in physical and psychological damage, as well as significant damage to the child’s growth and development. Objectives: To describe the medical approach to children who are victims of sexual violence, in order to provide guidance to medical professionals on how to manage pediatric patients in situations of abuse. Justification: This research is relevant as it helps in the process of conducting medical care for a child victim of sexual abuse. Methodology: This is an integrative literature review carried out in the SciELO, PubMed, MEDLINE and LILACS databases, using the DeCS: “Sexual Abuse in Childhood” and “Medical Assistance”. Combined with each other by the AND operator. Studies in Portuguese, English and Spanish were included, available online in full, in the last five years (2016-2021), repeated studies between databases and that did not address the theme were excluded. Results and Discussion: In view of the above, three categories of findings emerged, in order to solve the proposed objective, which are conceptual and legal aspects of sexual crimes, medical care in cases of sexual violence against children, effectiveness of care protocols. Final considerations: We can observe the importance of the doctor during the care of a child victim of sexual abuse. Considering that the doctor is the professional who provides the first care to the child, identifying the abuse and calling the police and the guardianship council.